Morphological and molecular identification of ticks collected from dogs (Canis lupus familiaris) with ehrlichiosis in Chiclayo, Peru - Cervantes S., Miguel (2020)
The present study aimed to identify morphologically and molecularly the ticks of dogs with ehrlichiosis in the Chiclayo district (Lambayeque, Peru). A total of 297 ticks from 74 dogs were collected and morphologically identified as Rhipicephalus sanguineus s.l. Nine specimens were used for molecular identification using the 16S rDNA ribosomal gene. The sequences obtained were aligned with sequences of R. sanguineus s.l. from Brazil and Colombia (Northern Lineage), Argentina, Chile and Uruguay (Southern Lineage), Spain, Italy and South Africa, showing a genetic divergence of 0-0.3% and 6.1-6.8% with the Northern Lineage and Southern Lineage, respectively. The phylogenetic analysis grouped the sequences of Peru with those of the Northern Lineage and South Africa, segregating them from the sequences of the Southern Lineage and Europe. The results show that R. sanguineus s.l. from Chiclayo, Peru, belongs to the Northern Lineage.